2014
DOI: 10.1111/jfd.12295
|View full text |Cite
|
Sign up to set email alerts
|

Purified deoxynivalenol or feed restriction reduces mortality in rainbow trout, Oncorhynchus mykiss (Walbaum), with experimental bacterial coldwater disease but biologically relevant concentrations of deoxynivalenol do not impair the growth of Flavobacterium psychrophilum

Abstract: Diets containing deoxynivalenol (DON) were fed to rainbow trout Oncorhynchus mykiss (Walbaum) for 4 weeks followed by experimental infection (intraperitoneal) with Flavobacterium psychrophilum (4.1 × 10(6) colony-forming units [CFU] mL(-1) ). Mortality of rainbow trout fed either 6.4 mg kg(-1) DON or trout pair-fed the control diet was significantly reduced (P < 0.05) in comparison with trout fed the control diet to apparent satiation (<0.1 mg kg(-1) DON). In a second experiment, trout were fed one of three ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 36 publications
(50 reference statements)
3
33
1
Order By: Relevance
“…Manning, et al [ 21 ] did not observe mortality of channel catfish fed diets containing high levels of DON (10 mg·kg −1 ) from naturally contaminated corn. Likewise, no significant difference in mortality of rainbow trout fed a diet containing 6.4 mg·kg −1 purified DON or fish pair-fed the control diet was observed by Ryerse, et al [ 51 ]. Interestingly, Manning, et al [ 21 ] demonstrated that feeding diets containing 5 and 10 mg DON kg −1 significantly decreased mortality of channel catfish during a trial of 21-day post-challenge with the pathogenic bacterium ( Edwardsiella ictaluri ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Manning, et al [ 21 ] did not observe mortality of channel catfish fed diets containing high levels of DON (10 mg·kg −1 ) from naturally contaminated corn. Likewise, no significant difference in mortality of rainbow trout fed a diet containing 6.4 mg·kg −1 purified DON or fish pair-fed the control diet was observed by Ryerse, et al [ 51 ]. Interestingly, Manning, et al [ 21 ] demonstrated that feeding diets containing 5 and 10 mg DON kg −1 significantly decreased mortality of channel catfish during a trial of 21-day post-challenge with the pathogenic bacterium ( Edwardsiella ictaluri ).…”
Section: Resultsmentioning
confidence: 94%
“…This finding was supported by Ryerse, et al [ 52 ], who observed a significant reductions in the cumulative mortality of rainbow trout fed diets containing 4.1 or 5.9 mg·kg −1 DON from naturally contaminated corn compared to control and pair-fed groups following infection with Flavobacterium psychrophilum . Likewise, feeding a diet containing 6.4 mg·kg −1 purified DON significantly reduced mortality of rainbow trout after experimental F. psychrophilum infection compared to the control group (<0.1 mg·kg −1 DON) [ 51 ]. The authors suggest that reduced feed intake associated with DON may positively influence survival during disease outbreaks [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although deoxynivalenol has been found to accumulate in the muscle of carps [130] and rainbow trout [126], it only did so at low levels. In fact, deoxynivalenol is usually rapidly metabolized and generally does not accumulate in the animal's organs.…”
Section: Effects On Fishmentioning
confidence: 94%
“…However, when doses of up to 2.6 mg/kg of this toxin were fed to rainbow trout, it resulted in feed refusal and reduction in feed conversion efficiency which, in turn, led to a reduction in weight gain and growth rate [123][124][125][126]. However, feeding rainbow trout a diet with 6.4 mg/kg of deoxynivalenol resulted in a reduction in mortality after Flavobacterium psychrophilum infection, although in parallel there was an increase in feed refusal [126,127]. Similarly, exposure of channel catfish to deoxynivalenol (2.5 to 10.0 mg/kg) increased their survival rate after Edwardsiella ictalurid infection, but with no negative effects on weight gain and feed conversion efficiency [128].…”
Section: Effects On Fishmentioning
confidence: 99%
“…Feed restriction in fish has also been associated with increased resistance to certain infectious pathogens. Rainbow trout Oncorhynchus mykiss (Walbaum) experimentally infected with Flavobacterium psychrophilum after a period of 4 weeks of preinfection nutrient restriction that continued for 3 weeks post‐infection had a significantly higher survival rate than fully fed controls (Ryerse, ; Ryerse, Hooft, Bureau, Hayes, & Lumsden, ). Feed restriction has also been demonstrated to reduce the number of mortalities in rainbow trout infected with Flavobacterium branchiophilum.…”
Section: Introductionmentioning
confidence: 99%